Regret and Rationalization Among Smokers in Thailand and Malaysia: Findings From the International Tobacco Control Southeast Asia Survey - Wonkyong B. Lee (2018)
Objective: To test whether differences of history and strength in tobacco control policies will influence social norms, which, in turn, will influence quit intentions, by influencing smokers' regret and rationalization. Design: The data were from the International Tobacco Control (ITC) Policy Evaluation Southeast Asia Survey, a cohort survey of representative samples of adult smokers in Thailand (N = 2,000) and Malaysia (N = 2,006). The survey used a stratified multistage sampling design. Main Outcome Measures: Measures included regret, rationalization, social norms, and quit intention. Results: Thai smokers were more likely to have quit intentions than Malaysian smokers. This difference in quit intentions was, in part, explained by the country differences in social norms, regret, and rationalization. Reflecting Thailand's history of stronger tobacco control policies, Thai smokers, compared with Malaysian smokers, perceived more negative social norms toward smoking, were more likely to regret, and less likely to rationalize smoking. Mediational analyses revealed that these differences in social norms, accounted, in part, for the country-quit intention relation and that regret and rationalization accounted, in part, for the social norm-quit intention relation. Conclusion: The results suggest that social norms toward smoking, which are shaped by tobacco control policies, and smokers' regret and rationalization influence quit intentions. © 2009 American Psychological Association.